Pelatihan Pembuatan Bahan Ajar Speaking Berbasis Rekayasa Faktor Kognitif (Task Complexity) bagi Guru-Guru SMA/SMK Di Kabupaten Pringsewu : INA - - Mahpul; Bambang Setiyadi; Muhammad Sukirlan; Gede Eka Putrawan (LPPM Universitas Lampung, 2021)
Task complexity-based learning approaches have been widely adopted in countries especially where English is a foreign language, Chinese, Japanese, Arabic, Iranian, and Korean. However, most English teachers do not yet understand the method of learning English based on task complexity so they lack confidence in applying the method.. Therefore, this community service activity aims to increase insight and knowledge about the development / creation of a speaking learning model based on cognitive factor engineering (task complexity). This activity will target English teachers at high school / vocational school in Pringsewu Regency and is expected to improve their professionalism to improve the quality of the English learning process, especially speaking. This activity will be carried out with lecture methods, discussions, practices, and simulations that will begin with a pre-test and end with a post-test. Based on initial and final abilities, there are quite real differences before and after the training is done. To that end, this training has been able to improve the insight and Manufacture of Teaching Materials Based on Cognitive Factor Engineering (Task Complexity). Some participants showed that the enthusiasm and belief of the participants that the Manufacture of Speaking Teaching Materials Based on Cognitive Factor Engineering (Task Complexity) has a positive impact to develop students' ability to master their English learning in the classroom.